Catch-up growth following early-life stunting in a low-resource area in rural Tanzania: the MAL-ED Metabolic study - Estomih Mduma; Samwel Jatosh; Mark D DeBoer; Eric R Houpt; Kiya Nemati; Yotham Z Michael; Bernadetha P Hhando (BMJ Open)
Background Poor linear growth over time can lead to stunting, a significant public health problem in low-resource settings. Catch-up growth, the process of accelerated growth following growth faltering, is important for mitigating the long-term impacts of early stunting. This study aimed to identify key predictors of growth over time, stunting and catch-up growth among children in rural Tanzania.Methods We evaluated 182 children from the Etiology, Risk Factors, and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development cohort, whose anthropometric measurements were collected at six points from birth to 11.5 years. We assessed outcomes of height-for-age z-score (HAZ), stunting and catch-up growth using mixed-model linear and logistic regression to assess associations of maternal education, household income, socioeconomic status, insulin-like growth factor 1 (IGF-1) and thyroid function tests. We defined stunting as HAZ ≤−2 and catch-up growth both as stunting resolved from age 2 years to 11.5 years and a HAZ increase of >0.5 from 2 years to 11.5 years.Results Cohort participants exhibited a moderate amount of catch-up growth, with per cent stunting decreasing from 72.6% at 2 years to 39.0% at 11.5 years. Maternal education, household income, socioeconomic status and IGF-1 were positively associated with HAZ (eg, IGF-1 point estimate 0.141±0.067, p=0.036) and negatively associated with odds of stunting across time points, while thyroid-stimulating hormone was negatively associated with HAZ and positively associated with odds of stunting (all p<0.05). For the definitions of catch-up growth, only IGF-1 was associated with odds of catch-up growth by both definitions (both p<0.01). Because of the potential for IGF-1 to be associated with maturation (and potential early growth cessation), we also assessed regression models that included IGF-1, luteinizing hormone and follicle-stimulating hormone, revealing that IGF-1 remained associated with catch-up growth (p<0.05).Conclusions These findings highlight the need for comprehensive interventions that address socioeconomic, hormonal and biological factors to promote catch-up growth and reduce stunting in resource-limited settings. The results offer valuable insights towards improving child health outcomes in similar contexts.Trial registration number NCT02441426 (post-results) and NCT05121935.